2021
DOI: 10.3390/antiox10091461
|View full text |Cite
|
Sign up to set email alerts
|

Plant Feed Additives as Natural Alternatives to the Use of Synthetic Antioxidant Vitamins on Livestock Mammals’ Performances, Health, and Oxidative Status: A Review of the Literature in the Last 20 Years

Abstract: In the last two decades, the interest in natural plant feed additives (PFA) as alternatives to synthetic vitamins in livestock nutrition has increased. After a systematic review, a total of 19 peer-reviewed papers published between 2000 and 2020 were retained to evaluate the antioxidant effects of PFA compared to synthetic antioxidant vitamins (mainly vitamin E; VitE) in livestock nutrition. These studies demonstrated that PFAs could be as efficient as VitE in counteracting oxidative stress in pigs, rabbits, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…In SG6 and SG5, the intake of tocols was mainly furnished by feed. Indeed, tocopherol-acetate is generally added to the poultry diets to improve the shelf life of meat, [ 49 ], greatly contributing to the tocols furnished by feed.…”
Section: Discussionmentioning
confidence: 99%
“…In SG6 and SG5, the intake of tocols was mainly furnished by feed. Indeed, tocopherol-acetate is generally added to the poultry diets to improve the shelf life of meat, [ 49 ], greatly contributing to the tocols furnished by feed.…”
Section: Discussionmentioning
confidence: 99%
“…Proanthocyanidins , one of the polyphenol compounds that are abundant in bearberry and green tea, has been proven to donate hydrogen atoms/electrons and to function as an antioxidant [ 39 , 40 ]). Second, with more hydroxyl groups present in the skeletons of plant extracts such as flavonoids, the plant extracts can potentially possess a higher capacity of antioxidants because they can provide more electrons [ 41 ]. Many studies have reported that phenolic compounds with higher hydroxylation, particularly those located ortho to one another (catechol moiety, namely, vicinal OH groups), exert extremely high antioxidant activities [ 42 , 43 ]).…”
Section: Plant Extracts and Their Anti-inflammatory And Antioxidant E...mentioning
confidence: 99%
“…Co., Ltd. Seoul, Korea), the cholesterol concentrations were measured phytobiotics, and acidifiers have all been investigated as nutritional supplements to assist offset the detrimental effects of elevated environmental temperature and heat stress (Awaad et al, 2018;Awad et al, 2020). When used as dietary supplements, a variety of tropical botanicals or phytogens show antioxidant action (Manuelian et al, 2021;Oloruntola et a., 2022). Prebiotics has been associated with an increase in the beneficial microbial population, whereas probiotics have been connected to a reduction in antioxidative stress in animals (Zhang et al, 2011;Awad et al, 2020).…”
Section: Collection Of Data Blood Samples and Data Analysismentioning
confidence: 99%